E-SDM KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SUMATERA SELATAN - Hutrianto, Hutrianto; Putra, Ade (Universitas Bina Darma, 2015)
This research wasdone to makethe software E-Human Resources Regional Office of Religious Affairs of South Sumatra Province. In this research, E-HR software can manage the data generated work routines include activity data consists of SK activities, KDP activities, treasurer of activities, number of activities, speakers, participants of the activities, the moderator, the cost of activities, presence, SPPD and reporting. E-HR software is made also to address the needs and transparencyin every activity performed. In software development E-SDM using software development Rational Unified Process (RUP) model. In RUP, there are four phases of work manship Inception Elaboration Construction and Transition.